IMPLEMENTATION OF FAMILY HOPE PROGRAM (PKH) POLICY IN TASIKMALAYA CITY IN 2016 (Policy Implementation of the Family Hope Program (PKH) In Tasikmalaya City 2016): - Dandan Haryono; Ishak Kusnandar; Ani Heryani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Based on the observation that the policy implementation of the Keluarga Harapan Program is still weak because of the following, Lack of regular companion meetings, unscheduled socialisation, including with community leaders, the general public, and aid recipients, There is no synergy between local governments as a coordinating team and implementers. Lack of understanding between implementors (assistants) in Tasikmalaya City The purpose of the study was to analyze the political implementation of the Family Hope Program (PKH) in Tasikmalaya City. The method used is qualitative, with descriptive analysis methods. Then the data collection techniques that the author uses are through literature studies and field studies, which include observation, interviews, and documentation; data analysis through data collection; data condensation; and conclusion drawing. The results showed that the interaction between policy makers and implementors was very minimal, and then the socialization of scheduled programs to the targets and stakeholders carried out by the person in charge was very lacking for various reasons and the absence of full responsibility of the person in charge charge of activities in the regions, thus making coordination blocked, especially with the emergence of socio-economic differences between various stakeholders and program targets. In conclusion, the Kelurga Harapan program in Tasikmalaya City is still not effective.